Factors associated with communication competence among surgical nurses - Laura Andrian Leal; Beatriz Regina da Silva; Lucieli Dias Pedreschi Chaves; Mirelle Inácio Soares; Daniela Sarreta Ignácio; Silvia Helena Henriques (Universidade Federal de Santa Maria, 2021)
Objective: to identify the factors associated with communication as competence among nurses in surgical centers. Method: exploratory, qualitative study. The participants were 43 nurses from five private hospital institutions in the countryside of Minas Gerais participated. The collection occurred in 2018 through six meetings of focus groups. The data were analyzed by inductive thematic analysis. Results: communication competence is associated with factors such as: care quality and safety, relationship in the work team, ways of communicating and interacting; computerization of the shift and interaction with other sectors of the institution. Conclusion: considering communication as an essential competence for surgical nurses, identifying factors that can influence it in a positive or limiting way should provoke the reflection of future professionals and managers in the development and implementation of strategies in the work environment that promote the development of effective communication.